EFFECT OF DIABETIC RETINOPATHY PROGRESSION ON VISUAL ACUITY IN TYPE II DM PATIENTS - Amin, Ramzi; Rajendra Ekki Maulana; Syarif Husin (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
This study aims to assess the effect of DR severity on visual acuity and to identify additional contributing factors. An observational analytic study with a cross-sectional design was conducted using medical records of Type II DM patients diagnosed with DR at Dr. Mohammad Hoesin General Hospital, Palembang, between January 2021 and October 2024. Statistical analysis was performed using Fisher’s exact test to evaluate significance, followed by logistic regression to determine the most influential factor. The results showed a significant association between DR severity and visual acuity (p=0.008), while other factors including macular edema (p=0.137), age (p=1.000), gender (p=1.000), intraocular pressure (p=1.000), HbA1c levels (p=1.000), and history of hypertension (p=1.000), were not significantly associated. In conclusion DR severity has a significant and dominant influence on the visual acuity of DR patients.